ANALISIS REDUKSI LIMBAH NITROGEN BERDASARKAN JENIS MEDIA TANAM DAN KONSENTRASI PROTEIN PAKAN BERBEDA PADA BUDIDAYA IKAN LELE DENGAN SISTEM AKUAPONIK - Euis Asriani; Ardiansyah Kurniawan (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2016)
Aquaponic technology is a bio-integrated farming system using resirculation of water from aquaculture to the plants and vice versa . It is a simple technology can be used to cultivate nonproductive land, even a narrow land to produce double production, namely fishes and plants. A basic principle from this technology is an application of zero waste aquaculture through water resirculation process contains fisheries organic waste that can be used as a nutrition for plants upon it. This research purposed to analyze the content of aquatic nitrogen waste gained from catfish aquaculture, know about significant influence of aquaponic to the ability of nitrogen waste reduction, and analyze the reduction ability of charcoal chaff and sawdust as a type planting from aquaponic. Based on the block random design with F-test gained that the differences of protein concentration on feed and types of planting media didn’t give a significant influence to the reduction of nitrogen waste, in this case ammonia and nitrit. But manually can be seen that charcoal chaff more effective in reducting ammonia and nitrit than sawdust.